DEEP BREATHING EXERCISE MANAGEMENT IN ARCHERY TO MEMORIZING AL-QUR'AN TO STUDENT OF TAHFIDZ QUR'AN AT SMP AD-DHUHA JEMBER - Akhmad Efrizal Amrullah; Ridlo Hafidz Faqih; Miftakhur Rohman; Candra Aditya Hermansyah (International Islamic Medicine Forum, 2021)
Memorizing Al-Qur'an is an effort to maintain the purity of the Al-Qur'an. The Qur'an tahfidz program is one of the activities intended to prevent the Qur'an from changing and falsifying either partially or completely. As the name implies, this program is applied to tahfidz Qur'an student to memorize Al-Qur'an under the guidance of their teacher. Memorization ability is determined by memory capacity which indicates brain health, one of which is influenced by the supply of oxygen to the brain. One way to maintain brain oxygenation is the management of deep breathing exercises combined with archery. The purpose of this study was to determine the effect of deep breathing exercises management in archery to achievement of memorizing the Qur'an. This research was held at SMP Ad-Dhuha Jember with a quasi-experimental one group pretest-posttest design method and was conducted in April-June 2019. The type of sample used was a total sampling of 34 respondents. Data analysis used the Wilcoxon Signed-Rank Test. The results showed an increase in the achievement of memorizing Al-Qur'an among students of the tahfidz Qur'an after managing deep breathing exercises with archery. Data analysis with alpha (α) <0.05 indicates a p value of 0.000 so that Ho is rejected. Thus there is an effect of deep breathing exercises management in archery on the achievement of memorizing the Al-Qur'an. A strong memory is needed to keep memorizing Al-Qur'an. To help increase the memory capacity of the brain, it requires an adequate supply of oxygen. Deep breathing exercises management combined with archery can be a way to maintain brain oxygenation. This exercise focuses on fullfiling oxygen needs, which in the process of memorizing the brain's memory functions are widely used.